The systemic fibrinolytic activity of intrapleural streptokinase - Davies, C; Lok, S; Davies, R (1998)
Intrapleural fibrinolytics probably improve the drainage of loculated pleural effusions and empyemas. Studies of crude indices of systemic coagulation suggest this effect is accompanied by little systemic fibrinolysis, but few studies have assessed this in detail. This study examines the systemic fibrinolytic activity of two intrapleural streptokinase (IPSK) regimes in detail. Eight patients received a single dose of 250,000 IU IPSK, and a further eight received serial doses of 250,000 IU IPSK every 12 h for 3 d (total dose: 1.5 million IU). Each dose was retained in the pleural cavity for 2 h. Venous blood for prothrombin time, activated partial thromboplastin time, thrombin time, fibrinogen, and D-dimers due to fibrin degradation were measured before any IPSK. These end points were then remeasured 24 h after IPSK in the single-dose group and after 24, 48, and 72 h in the group receiving serial doses. There were no physiologic or statistical differences in any of the indices after administration of IPSK. IPSK administered up to a dose of 1.5 million IU does not cause significant activation systemic fibrinolysis in humans.